Tabanja: Ett exempel på etnografisk fiktion - Silow Kallenberg, Kim (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2017)
This article is about ethnographic knowledge production, and is an investigation of the forms that knowledge production can take. The text consists of two separated parts; a contextualising introduction and a short story based on the material of ethnographic fieldwork. The aim is to highlight parts of human life that are hard to depict with traditional scholarly genres. In the first part of the article – the introduction – the relation between subjectivity and objectivity in ethnographic research, and the blurred lines that often exist between the two, is used as a point of departure to argue for the use of ethnographic fiction in research processes. Concepts such as thick description and self-reflexivity are used in the discussion. Ethnographic fiction can have multiple meanings and is here understood as fiction based in ethnographic knowledge. This genre can be a means to highlight aspects that are excluded or toned down in more traditional academic texts. Ethnographic fiction can also be a means to communicate research results to other audiences than the ones that normally reads scholarly works. The second part of the article consists of an example of ethnographic fiction in the form of a short story. The story is about a young boy named Issa, who grows up in a marginalised community and who leads a destructive life that eventually results in him being subjected to compulsory care. Issa is a fictional character with a real life role model in one of the authors’ research persons that were shot and killed only sixteen years old.